Augmented Reality and Student Motivation: A Systematic Review (2013-2024) - Ruijia Zuo; Li Wenling; Zhang Xuemei (Scientia Publica Media, 2025)
This study investigates the impact of Augmented Reality (AR) technology on K-12 students’ learning motivation. AR, as an innovative instructional tool, integrates virtual objects into real-world settings, creating immersive and interactive learning environments. Learning motivation is a critical factor influencing students’ academic achievement, and AR technology provides autonomous and personalized learning experiences that enhance capabilities, reduce cognitive load, and improve learning outcomes. A systematic literature review methodology was adopted, analyzing 44 high-quality research articles published between 2013 and 2024 that examine the relationship between AR and learning motivation. The analysis revealed that AR technology is widely implemented in educational contexts, particularly in subjects such as mathematics, science, and art, offering authentic and engaging learning experiences. The findings highlight that AR significantly enhances students’ learning motivation by fostering autonomy, promoting interactive activities, and visualizing abstract concepts in intuitive ways. These features reduce cognitive load and improve comprehension, leading to better academic performance. Additionally, the novelty of AR stimulates students’ curiosity, driving sustained engagement and making learning more appealing and effective. The study underscores the potential of AR to transform traditional education by creating engaging and interactive learning experiences. Educators are encouraged to integrate AR into their instructional practices to foster students’ curiosity, motivation, and academic success. Future research should explore the long-term effects of AR technology and address challenges such as accessibility and teacher training to maximize its impact in educational settings.